Zakres mocy wiążącej wykładni sądowej: [Scope of the binding force of judicial interpretation] (Studia Prawnicze / The Legal Studies, 1969)
Autor w niniejszej pracy przedstawia zagadnienie dokonywania przez sądy wykładni prawa o mocy wiążącej. Kładzie szczególny nacisk na analizę zakresu mocy obowiązującej wykładni. Prezentuje klasyfikacje przypadków wiążącej wykładni sądowej w prawie polskim. Ponadto autor opisuje przypadki wykładni indywidualnej, która występuje w dwóch przypadkach tj. w kasatoryjnym orzeczeniu sądu wyższego oraz wykładni zawartej w odpowiedzi Sądu Najwyższego na pytanie prawne sądu II instacji. Przedstawiono również zagadnienia dotyczące wykładni ogólnej, skupiając się na rozważaniach dotyczących podmiotowego i przedmiotowego zakresu wiązania wykładnią sądową. In this paper, the author presents the issue of courts interpreting the law with binding force. He places particular emphasis on analysing the scope of the validity of an interpretation. He presents classifications of cases of binding judicial interpretation in Polish law. In addition, the author describes cases of individual interpretation, which occurs in two cases, i.e. in a cassation decision of a higher court and the interpretation contained in the Supreme Court's answer to a legal question of a court of second instance. Issues of general interpretation are also presented, focusing on considerations of the subjective and material scope of binding judicial interpretation.